I Feel Anxious When Communicating: Questioning Students’ Learning Readiness - Jusuf Blegur, Ramona M. Mae & Mieke Souisa (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
When learning process occurs, the educators expect students’ fully participation.However, learners experience various obstacles in their participation efforts, suchas feelings of anxiety during presentations and discussions. This study aims toinvestigate students’ anxiety predictors when doing communication during thedynamic learning. There are 2 males and 2 female participants (4 participants)involved. Their anxiety problems in communication will be explored usingqualitative approach. In order to obtain data on factors triggering participants’anxiety, researchers used participation-observation techniques on each ofparticipant’s activity and behavior in the classroom and conducted in-depthinterviews to reveal what experiences contributing to participants’ anxiety. Theresults found that factors that cause the participants to feel anxious whencommunicating are: 1) Limited mastery of the material, 2) Ignoring the activity ofself expression in the learning, 3) Lack of confidence, 4) Being trapped intraumatic sense, and 5) Crisis of appreciation toward learning effort from the peers.Keywords: [Anxiety; communicating; learning readiness]